Production of biodiesel from a non-edible source and study of its combustion, and emission characteristics: A comparative study with B5 - Abedin, M.J.; Kalam, M.A.; Masjuki, Haji Hassan; Sabri, M.F.M.; Rahman, S.M.A.; Sanjid, A.; Fattah, I.M.R. (Elsevier, 2016)
This investigation deals with the production of Alexandrian laurel (Calophyllum inophyllum) biodiesel (ALB) and study of the effects of its fatty acid methyl ester (FAME) compositions and physicochemical properties on the engine performance, combustion, and emissions. The experiment had been conducted in a four cylinder turbocharged diesel engine under varying speeds and full loading condition. 10% (ALB10) and 20% (ALB20) blends of Alexandrian laurel biodiesel along with the Diesel and B5 fuel (95% diesel and 5% palm biodiesel) were used for this experiment. ALB consisted of 31.6% saturated and 68.4% unsaturated FAME. Longer chain fatty acids and 10.9% oxygen content of ALB greatly influenced the engine combustion and emission characteristics. Brake specific fuel consumption (bsfc) was found on average 6%-20% higher for B5, ALB10, and ALB20 blends compared to diesel fuel. It was observed that ALB operation shortened the ignition delay period, increased the mass fraction burnt (MFB), and reduced the pick cylinder pressure, heat release rate (HRR) and combustion duration. CO and HC emissions were decreased significantly while operating on B5, ALB10, and ALB20 blends compared to diesel fuel. ALB blends produced on average, 2.5%-3% higher NOX emissions with respect to diesel fuel.